Islamophobia and Values in Western Societies: An Analysis of the Impacts on Muslim Men of Islamophobic Attacks in the UK - Durali Karacan (Değerler Eğitimi Dergisi)

(untitled)
The populations and governments of Western societies are usually proud of the values they claim to be the foundation of their multicultural and pluralistic societies. Over the past few decades, the Western world has witnessed a surge in hate crimes, including racism, discrimination, and Islamophobia. This has sparked discussions about the authenticity of Western societies in upholding universal or Western values. The main purpose of this study is to investigate the impact of Islamophobia on universal or Western values. It is crucial to clarify that the research does not seek to make sweeping generalizations about these values. Instead, its focus is a thorough examination of the decline in the beliefs of Muslim men in these values, particularly in response to the growing incidents of Islamophobic attacks. The study delved into two specific Islamophobic assaults to shed light on the concerning extent of Islamophobia, suggesting a potential threat to both universal and Western values as well as social cohesion in the UK. Through individual semi-structured and in-depth interviews, Muslim men residing in the UK were engaged to explain the repercussions of these distressing Islamophobic incidents on their lives, perspectives, and notably, their beliefs in universal or Western values. The findings of the study revealed that acts of Islamophobic violence, particularly those directed at vulnerable and disabled Muslims, have a detrimental impact on the beliefs of Muslim males in the UK regarding universal or Western principles and values. The Muslim men in the study strongly criticised the bystanders in these incidents, expressing their disappointment in the lack of protection for the vulnerable and disabled victims, while emphasizing the link between “bystander apathy” and societal values. Additionally, participants underscored the importance of incorporating Islamic values into the education of their children.